HUBUNGAN STATUS SOSIAL EKONOMI ORANG TUA DENGAN HASIL BELAJAR KOMPETENSI PERAWATAN KULIT WAJAH BERMASALAH SISWA KELAS XI SMK NEGERI 6 PADANG - rodiah, rodiah; katin, yusmar emmy; hayatunnufus, hayatunnufus (Journal of Home Economics and Tourism, 2013)
The puprpose of this study is to see the relationship between parent’ seconomic and social statue to student’s study achievement at competition makingup of unwell face skin at SMKN 6 Padang. The form of this study is chorelationquantitative.  Population in this study is the 11th competent of keahlian tatakecantikan SMKN 6 Negeri Padang. Sampel of this study is the whole ofpopulation that consist of 30 student by using total sampling technique.  To knowof parent’s economic social statue, we use questioner which validity andrealibility is tested. Then to test the hypothesis is used chorelation test pearsonproduct moment.  Based on this study we can conclude that first, stage of thehighest respondent achievement  variable of parent’s economic and social statueare in lowest category (36,6%). Second, variable of student’s study achievementat competition making up of unwell face skin is not completed  as  much as 66,6%. Third, there are positive and significan relationship between parent’s economicand social statue to student’s study achievement.  Kata kunci : Status Sosial Ekonomi, Orang Tua, Hasil Belajar,